Teaching resources for environmental education: do the official materials reach the basic education classroom? - Pipitone, Maria Angélica Penatti; Dallóca, Laura Ichimaru; Miranda, Allan Douglas de (Revista Hipótese, 2015)
The objective of the research was to identify whether the official work of the Ministry and Departments of Education and Environment reach the public schools classrooms to equip the teacher's educational practice. At the same time, a sample of fifty two science teachers answered a questionnaire. About half of the participants use the official materials for environmental education and they also use videos, magazines, textbooks and other materials for the same purpose.
Keywords: environmental education; Teaching resources; Elementary school